Activity, work and employment: some reflections on a topic under debate - Neffa, Julio César (1999)
Since ten years ago, it is intensely thought of human work and employment in developed countries as a consequence of the deep changes on the productive system. In this chapter we analyze at first place the concept of work and its evolution, based on recent researches. In second place we review the notions of activity, work and employment and also the definition and measurement of unemployment, which is not a very old notion. The third part is about the work rol in human life and finally we study the different alternatives on activity and specific work contracts, proposals that nowadays replace the notion of "full employment" in France.